Interpretation of Moral Elements in the ITE Law on the Phenomenon of Digital Cosplayer Soft Erotica: Protection of Public Morals and Freedom of Expression - Athalaric Ghalib Pradana; Yati Nurhayati (Fakultas Studi Islam Universitas Islam Kalimantan Muhammad Arsyad Al Banjary, 2025)
The emergence of digital cosplayer soft erotica challenges the interpretation of “indecent content” under Article 27(1) of Indonesia’s Electronic Information and Transactions Law. The absence of a clear legal definition of indecency blurs the boundary between artistic expression, sensual content, and pornography, creating legal uncertainty. Using normative legal research with statutory, conceptual, and case approaches, this study analyzes the construction of indecency within the UU ITE and its relation to the Pornography Law. The findings indicate that soft erotica does not meet the statutory criteria of pornography due to the absence of explicit sexual activity, yet it occupies a regulatory grey zone that may still be categorized as indecent based on fluid public morality standards. Comparative analysis reveals the lack of objective legal indicators, underscoring the need for clearer interpretive frameworks to balance public morality protection with digital freedom of expression.